Upaya Orang Tua Menumbuh-Kembangkan Karakter Islami Anak Melalui Pembiasaan Mengaji di Taman Pendidikan Al-Qur’an (TPQ) Darul Muttaqin Benculuk Banyuwangi - Rosi Afianingsih (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
Cultivating a good and noble character is the complete responsibility of parents, both hablun minallah, hablun minannas and hablun minal alam. One of the efforts is through the habit of reciting the Koran in the Al-Qur'an Education Park (TPQ). This activity is per the concept of Ki Hajar Dewantara's Tri-Center for Education, namely that informal, formal, and non-formal education are related and complement each other in developing children's character. This study aims to describe the efforts of parents in cultivating the Islamic character of their children through the habit of reciting the Koran at the Darul Muttaqin Benculuk Educational Park in Banyuwangi. This research uses a qualitative case study approach: Collecting data using participant observation, semi-structured interviews, and documentation. The study concluded that good character is formed through the activities like enforcing prayer, fasting, zakat, praying and being grateful, helping each other, forgiving each other, being polite and courteous, littering, loving animals, and caring for each other plants.